Reducing emissions from deforestation and forest degradation (REDD) in Peru: a challenge to social inclusion and multi-level governance - Fariborz Zelli; Jonas-Ibrahim Hein; Daniela Erler; Anna-Maria Santa Cruz Melgarejo (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
REDD is one of the latest additions to a series of incentive-based mechanisms for reducing carbon emissions. Many developing and emerging countries have started engaging in REDD. Peru, the country with the world's fourth largest area of tropical forest, is no exception here – with an obvious motivation: about half of Peru's annual greenhouse gas emissions are currently caused by deforestation. Over the last years, public and private initiatives have led to a complex multi-level REDD governance architecture in Peru. This architecture faces challenges in terms of social inclusion and coordination. This study identifies and analyses key issues, some of which are merely teething problems, while others are deeply rooted in socio-economic imbalances and political culture, such as insufficient financial, technical and human capacities of ministries and regional governments; legitimacy gaps; and information and participation asymmetries across public actors, NGOs, companies and forest users. The study presents policy recommendations for addressing some of these challenges. These include: streamlining REDD processes with policies of other sectors; formalizing channels of communication and consultation; and providing a clear legal and institutional framework that encompasses the push and pull factors driving deforestation in Peru.
Keywords: 330; Landwirtschaft und ländliche Entwicklung; Umwelt; Ökosysteme und Ressourcen